Firms Intangible Assets and Multinational Activity: Joint-Venture Versus FDI - Valeria Gattai (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper provides a theoretical formalisation of the joint-venture contract, as an alternative to Foreign Direct Investment (FDI), within a Dissipation of Intangible Assets framework. In a two-period, two-country equilibrium model, we discuss how the threat of knowledge spillover shapes the boundaries of a Multinational Enterprise. Similarly to the theoretical findings on the FDI-licensing trade off, we show that Foreign Direct Investment is more likely to emerge when know-how easily spills over i.e. when firms are endowed with more intangible assets or they belong to high tech industries. Probit estimates, from an entirely new firm-level dataset, constructed by the author, show that the experience of Italian multinationals in Asia is in line with our theoretical predictions.
Keywords: F23; C25; O5; 330; Intangible assets; Internalisation; FDI; Joint-venture; Asia; Immaterielles Anlagevermögen; Joint Venture; Direktinvestition; Internationale Markteintrittsstrategie; Italien; Asien